Enantioselective Liquid–Liquid Extraction of Zopiclone With Mandelic Acid Ester Derivatives. Issue 12 (30th September 2013) - Peng, Yangfeng; He, Quan; Zuo, Bin; Niu, Haibo; Tong, Tianzhong; Zhao, Hongliang
ABSTRACT Enantioselective liquid–liquid extraction of zopiclone was conducted by employing a series of (R)‐mandelic acid esters as chiral extractants. The effects of concentration of extractant, concentration of zopiclone, type of organic solvent, pH value, and temperature on the extraction efficiency were investigated. (R)‐o‐chloromandelic acid propyl ester was demonstrated to be an efficient chiral extractant for zopiclone resolution with a maximum enantioselectivity of 1.6. Chirality 25:952–956, 2013. © 2013 Wiley Periodicals, Inc.